CHRONIC TOXISITY EFFECTS OF HERBICIDE, ATRAZINE ON BEHAVIOUR RESPONSE & BLOOD METABOLITE OF Clarias batrachus (Linn.) (International Journal of Food and Nutritional Sciences, 2023)
Atrazine (2-chloro-4-ethylamino-6-isopropylamino-s-triazine) is an herbicide widely used to weeds control in agriculture practice. The present study includes the blood metabolites alterations in airbreathing fish, Clarias batrachus (Linn.) induced to sublethal concentration (4 mg/L) of inorganic herbicide, atrazine. The treated fish group was showed significant blood biochemical alteration in the form of hyperglycemia, hypoproteinemia and hyperchlosterolemia diseases. Therefore the study reflect herbicide, atrazine at conc. 4 mg/l caused severe metabolic dysfunction in the fish Clarias batrachus. So, for optimum growth performance and survival rate of fish culture, water condition may be suitable at concentration of < 4 mg/L of atrazine contamination.